Determinants of Low Birth Weight; Its Impact On Early Childhood Morbidity and It’s Prevention in A Tertiary Care Hospital - Hanniya Naveed, Aftab Alem Jehangir, Kiran Khan, Junaid Ghaffar, Muhammad Uzair, Mustansar Billah (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To identify the determinants of low birth weight and to evaluate its impact on early childhood morbidity in a tertiary care hospital. Materials and Methods: This hospital-based observational study included 300 live-born neonates and was conducted over a period of 12 months from July 2022 to August 2023. Newborns were categorized into LBW (<2500 g) and normal birth weight (NBW ≥2500 g) groups. Maternal demographic, socioeconomic and clinical data were collected through interviews and medical records. Infants were followed for six months to assess morbidity patterns, including respiratory infections, diarrheal diseases, feeding difficulties and hospital admissions. Statistical analysis was performed using chi-square test, t-test and multivariate logistic regression, with a p-value <0.05 considered significant. Results: The prevalence of LBW was 32% (n=96). Maternal anemia (61.5% vs 28.4%), inadequate antenatal care (54.2% vs 22.5%), pregnancy-induced hypertension (27.1% vs 11.3%) and preterm birth (58.3% vs 14.2%) were significantly associated with LBW (p<0.05). Multivariate analysis identified maternal anemia (AOR=2.8), inadequate antenatal care (AOR=3.2) and preterm delivery (AOR=4.5) as independent predictors. During the six-month follow-up, LBW infants had higher rates of respiratory infections (46.9% vs 21.6%), diarrheal illness (39.6% vs 18.1%), feeding difficulties (29.2% vs 11.8%), and hospital admissions (34.4% vs 12.7%) (p<0.05). Additionally, 42.7% of LBW infants were underweight at six months compared to 17.6% of NBW infants. Conclusion: Low birth weight is strongly associated with modifiable maternal risk factors and significantly contributes to increased early childhood morbidity and poor growth outcomes. Strengthening antenatal care, improving maternal nutrition, and ensuring close postnatal follow-up of LBW infants are essential strategies to reduce its burden and improve child health outcomes. Keywords: Low birth weight, maternal anemia, antenatal care, preterm birth, early childhood morbidity, tertiary care hospital